2023
DOI: 10.4236/as.2023.143023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation under Semi-Controlled Conditions of the Pathogenicity of Three Isolates of <i>Phaeoisariopsis personata</i> (Berk. & M.A Curt.)

Abstract: Peanut (Arachis hypogaea L.) late leaf spot is an important disease caused by Phaeoisariopsis personata (Berk. Et M. A Curt.). This fungus is responsible for the most damaging leaf spots in peanut production. The present experiment was undertaken to evaluate the pathogenic variability of Phaeoisariopsis personata in Burkina Faso. To this end, detached leaves and healthy plants of three peanut varieties were inoculated. Isolates I3TF, I2TG and I1TK of the pathogen (10 5 conidia/ml), collected respectively in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The highest defoliation was obtained with I3TF Isolate from the Upper Basins region, the second wettest region in the country, studying the action of isolates on the same groundnut variety under the same controlled treatment conditions and observing the different results on defoliation and reduction would indicate the existence of variable effects of isolates from each climatic zone. These results corroborate those of [10], who found that the isolate from the Upper Basins region was much more severe than those from the Central and Eastern regions because of the very high late leaf spot severity scores it caused on groundnuts with high incidence of the disease. The percentage of defoliation due to late leaf spot being correlated with the severity of the disease [23] would then explain the difference in the impact of the isolates on defoliation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The highest defoliation was obtained with I3TF Isolate from the Upper Basins region, the second wettest region in the country, studying the action of isolates on the same groundnut variety under the same controlled treatment conditions and observing the different results on defoliation and reduction would indicate the existence of variable effects of isolates from each climatic zone. These results corroborate those of [10], who found that the isolate from the Upper Basins region was much more severe than those from the Central and Eastern regions because of the very high late leaf spot severity scores it caused on groundnuts with high incidence of the disease. The percentage of defoliation due to late leaf spot being correlated with the severity of the disease [23] would then explain the difference in the impact of the isolates on defoliation.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with the results of [31], who found that the site from which the isolate originated was favorable to late-leaf spot. [10] found that isolates from this site were more virulent than those from the eastern and central regions of the country, and consequently caused greater defoliation and a significant reduction in groundnut yield. This would explain why treatments with I3TF cause the greatest reduction in yield, regardless of the variety.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation